Crystal structure of Pseudomonas aeruginosa condensing enzyme PqsBC - Prasetya, Fajar (2018)
Pseudomonas aeruginosa is an opportunistic bacterium that can infect immunocompromised people, and is especially prevalent in patients with cystic fibrosis. Treatment of P. aeruginosa is complicated due to resistance to many classes of antibiotics. This is partly due to biofilm formation, which is not simply a diffusion barrier, but also has a distinct mechanism for resisting the action of antibiotics. P. aeruginosa quinolone signal (PQS) has an important role in quorum sensing, which is involved in biofilm formation. PqsBC is a condensing enzyme in the biosynthesis of the PQS. The crystal structures of PqsBCC129A and PqsBCC129A-Fe3+ were collected to 2.04 Å and to 2.3 Å, respectively. The crystal structure showed that PqsB and PqsC have a pseudo 2-fold symmetry that mimics the FabH homodimer as well as the presence of a catalytic diad instead of the typical catalytic triad in PqsBC, seen in other FabH family enzymes. The PqsCC129A active site volume is twice the volume as those of FabH enzymes or PqsD, with a calculated volume of 761Å3, compared to 389Å3 for PqsD and 367Å3 for FabH.The PqsBCC129A-Fe3+ crystal structure shows that Fe3+ binds to nitrogen atoms from PqsB His282 and PqsC His2 along with oxygen atoms from PqsB Glu48 and Glu280. Therefore, there are four bonds involved in the interaction between Fe3+ and PqsBCC129A. These bond lengths are very similar to those observed in the structures of Azurin and FutA1 complexed with iron. These crystal structures of PqsBC provide a unique insight into substrate recognition and establish a scaffold for structure guided drug design of novel antimicrobial agents.